Episodic memory assessment: effects of sex and age on performance and response time during a continuous recognition task - Clifford, James O.; Anand, Sulekha; Tarpin-Bernard, Franck; Bergeron, Michael F.; Ashford, Curtis B.; Bayley, Peter J.; Ashford, John Wesson (Frontiers in Human Neuroscience, 2024)
Introduction: Continuous Recognition Tasks (CRTs) assess episodic memory (EM), the central functional disturbance in Alzheimer’s disease and related disorders. The online MemTrax computerized CRT screening and assessment that is engaging and can be repeated frequently. MemTrax presents complex visual stimuli, which require involvement of the lateral and medial temporal lobes and can be completed in less than two minutes. Results include number of correct recognitions (HITs), recognition failures (MISSes=1-HITs), correct rejections (CRs), false alarms (FAs=1-CRs), total correct (TC=HITs+CRs), and response times (RT) for each HIT and FA. Prior analyses of MemTrax CRT data show no effects of sex but an effect of age on performance. The number of HITs corresponds to faster RT-HITs more closely than TC, and CRs do not relate to RT-HITs. RT-HITs show a skewed distribution, and cumulative RT-HITs fit a negative survival curve (RevEx). This study aimed to define precisely the effects of sex and age on HITS, CRs, RT-HITs, and the dynamics of RTs in an engaged population. Methods: MemTrax CRT online data on 18,255 individuals was analyzed for sex, age, and distributions of HITs, CRs, Misses, FAs, TC, and relationships to both RT-HITs and RT-FAs. Results: HITs corresponded more closely to RT-HITs than did TC because CRs did not relate to RT-HITs. RT-FAs had a broader distribution than RT-HITs and were faster than RT-HITs in about half of the sample, slower in the other half. Performance metrics for men and women were the same. HITs declined with age as RT-HITs increased. (? FAs) The group over aged 50 years had RT-HITs distributions slower than under 50. For both age ranges, the RevEx model explained more than 99% of the variance in RT-HITs. Discussion: The dichotomy of HITs and CRs suggests opposing cognitive strategies and effects on processing speeds: 1) less certainty about recognitions, in association with slower RT-HITs and lower HIT percentages suggests recognition difficulty, more MISSes, and 2) decreased CRs (more FAs) but faster RTs to HITs and FAs, suggesting overly quick decisions leading to errors. This CRT provides potential clinical screening utility for early Alzheimer’s disease and other conditions affecting EM.